The Effectiveness Service of Administration System and Village Information (SAID) Bondowoso District (Universitas Terbuka, 2023)
Bondowoso Regency Government as a public service provider has a strategy in solving problems in its territory. Problems that arise in the quality of service in rural areas are still manual and not systematic. The constrained service related to data collection is not yet electronic based so it is not evenly distributed and takes a long time. In addition, high dependence on employees in the process of public services without the ability to use excellent service technology. This is what underlies the Bondowoso Regency Government to develop a strategy with the Village Administration and Information System (SAID). The solution provided is in the form of utilizing information technology in order to improve the quality of administrative services by the village government to the community in Bondowoso Regency. Service effectiveness determines the SAID program in assessing the program's success in meeting community needs. This research uses a descriptive qualitative method in accordance with the guidelines and data processing. The data obtained from this study came from field studies by conducting in-depth observations and interviews. The results of this study discuss the use of effectiveness indicators from Gibson, et al (1996) with 6 indicators namely productivity, quality, satisfaction, efficiency, flexibility, and development in assessing the Village Administration and Information System in Bondowoso Regency. Referring to the results of the research discussion, it can be concluded that the use of SAID by measuring effectiveness can solve village administration service problems in Bondowoso Regency. Although there are several problems that have not been thoroughly resolved in areas that have not been reached and the lack of quality human resources in village officials in maximizing the use of SAID.